The influence of number of high risk factors on clinical outcomes in patients with early-stage cervical cancer after radical hysterectomy and adjuvant chemoradiation - Lim, Soyi (Obstet Gynecol Sci, 2016)
OBJECTIVE: The purpose of this study was to evaluate the prognosis according to the number of high risk factors in patients with high risk factors after radical hysterectomy and adjuvant chemoradiation therapy for early stage cervical cancer. METHODS: Clinicopathological variables and clinical outcomes of patients with FIGO (International Federation of Gynecology and Obstetrics) stage IB1 to IIA cervical cancer who had one or more high risk factors after radical hysterectomy and adjuvant chemoradiation therapy were retrospectively analyzed. Patients were divided into two groups according to the number of high risk factors (group 1, single high risk factor; group 2, two or more high risk factors). RESULTS: A total of 93 patients were enrolled in the present study. Forty nine out of 93 (52.7%) patients had a single high risk factor, and 44 (47.3%) had two or more high risk factors. Statistically significant differences in stage and stromal invasion were observed between group 1 and group 2. However, age, histology, tumor size, and lymphovascular space invasion did not differ significantly between the groups. Distant recurrence occurred more frequently in group 2, and the probability of recurrence and death was higher in group 2. CONCLUSION: Patients with two or more high risk factors had worse prognosis in early stage cervical cancer. For these patients, consideration of new strategies to improve survival may be worthwhile. Conduct of further clinical trials is warranted for development of adjuvant treatment strategies individualized to each risk group.